2019
DOI: 10.1038/s41467-019-12437-6
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis of catalyst composition during gold catalyzed GaAs nanowire growth

Abstract: Semiconductor nanowires offer the opportunity to incorporate novel structures and functionality into electronic and optoelectronic devices. A clear understanding of the nanowire growth mechanism is essential for well-controlled growth of structures with desired properties, but the understanding is currently limited by a lack of empirical measurements of important parameters during growth, such as catalyst particle composition. However, this is difficult to accurately determine by investigating post-growth. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 71 publications
(95 reference statements)
6
80
0
Order By: Relevance
“…Unlike top-down techniques, the “bottom-up” approach is based on molecular recognition and chemical self-assembly of molecules, which allows obtaining structures with sizes that can vary from a few nanometers to several microns. This approach, in turn, includes different methodologies, among which it is worth mentioning vapor-phase growth [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], liquid-phase growth [ 51 , 52 ], template-assisted etching [ 53 , 54 , 55 , 56 , 57 ], and electrospinning [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Synthesismentioning
confidence: 99%
“…Unlike top-down techniques, the “bottom-up” approach is based on molecular recognition and chemical self-assembly of molecules, which allows obtaining structures with sizes that can vary from a few nanometers to several microns. This approach, in turn, includes different methodologies, among which it is worth mentioning vapor-phase growth [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], liquid-phase growth [ 51 , 52 ], template-assisted etching [ 53 , 54 , 55 , 56 , 57 ], and electrospinning [ 58 , 59 , 60 , 61 , 62 ].…”
Section: Synthesismentioning
confidence: 99%
“…Further details of the experimental setup can be found in previous publications. 42,54 The layer growth dynamics is recorded as videos made up of a series of TEM images. The growth of each layer is identified as a dynamic change in the contrast at the interface.…”
Section: Data Acquisition and Measurementsmentioning
confidence: 99%
“…The first two layers that nucleated after the catalyst solidified had shorter incubation time compared to the later layers (Figure 2 a and Supporting Information Figure S2). This can be attributed to a transient effect, as the particle initially has a higher supersaturation due to excess Ga just after solidification (according to the phase diagram 42 Ga solubility in the solid phase is lower than the Ga concentration of liquid Au-Ga). Since the layer completion is expected to be limited by As availability 40 (due to the low solubility of As in the Au-Ga system 36,[42][43][44][45][46] ), the excess Ga is not expected to influence the layer completion time.…”
mentioning
confidence: 99%
“…Kim and co-workers [47] grew nanoneedles in the pure WZ phase on top of NWs by controlling the V:III ratio and proved that the formation of WZ phase nanoneedles is related to the droplet contact angle. In 2019, Maliakkal and co-workers [48] used an in situ electron microscope and X-ray energy dispersive spectroscopy to measure the catalyst composition during NW growth. They studied the growth of Au-seeded GaAs NWs and found that the Ga content in the catalyst during growth increased with both temperature and Ga precursor flux.…”
Section: Gaas Nw Growth and Crystal Phase Controlmentioning
confidence: 99%